PHYSICAL, CHEMICAL, AND MICROBIOLOGICAL PROPERTIES OF TILAPIA FISH AS AFFECTED BY CHARCOAL, ELECTRIC GRILLER, AND FIREWOOD HEAT SOURCES - Awolomate , Samuel; Oshibanjo, D. O; Mohammed, M. Y.; Anthony, Benjamin; Dashe, M. P. (Nigerian Journal of Agriculture and Agricultural Technology, 2022)
The influence of three heat sources on the physicochemical composition and meat quality of Tilapia (Oreochromis niloticus) was investigated. The fish farm produced twelve Oreochromis niloticus weighing an average of 65825 grams each. The fish were gutted and washed with distilled water to eliminate filth and blood; the dressed weights were then smoked. Smoking was accomplished using charcoal, wood, and an electric grill. Study examined the product’s production, pH, water-holding capacity (WHC), and oxidative rancidity. A sensory analysis and microbiological count were conducted in accordance with standard procedures. The data were analyzed using 0.05-level one-way ANOVA and graph pad prism. Compared to firewood and electricity, cooking Tilapia with charcoal yielded the highest output. Tilapia prepared over a firewood heat source had a pH of 6.62, whereas those prepared over an electric heat source had a pH of 6.56. At 54.44 percent, the Tilapia using an electric heat source had the highest Water holding capacity (WHC). There was a statistically significant difference (P0.05) in the Oxidative Rancidity, with the electric heat source Tilapia fish having the highest level at 0.31 mg/g. In terms of appearance, electric heat source Tilapia fish was preferred to firewood and charcoal heat source Tilapia fish; nevertheless, it was inferior in terms of taste, tenderness, texture, and salinity. Firewood-heated Tilapia fish had the best texture, but the worst flavor. This study found that electric heat sources for smoking Tilapia fish might be used without impacting nutritional content or consumer acceptability.